DIGITAL SKILL ASSESSMENTS: PRE & POST COVID - Anwar, Nurul Ain Khairul; Shuib, Nor Atiqah Mohd; Mohd Danuri, Mohd Shahrul Nizam; Mohd Shuib, Nor Liyana (Malaysian Journal of Computer Science, 2024)
This study explores the evolution of digital skills assessment between pre- and post-COVID, focusing on how the COVID-19 pandemic accelerated both the urgency and complexity of evaluating digital competence across sectors. Prior to 2020, assessment frameworks emphasised basic ICT skills that were often evaluated through standardised and summative tools. However, the global shift to remote education, telehealth, and virtual work exposed critical gaps in adaptability, contextual fluency, and digital resilience skills not captured by traditional assessments. Through a systematic narrative review of academic literature and institutional reports, this paper analyses key trends, frameworks, and innovations that have emerged in the post-pandemic era. The findings show a marked transition toward formative, adaptive, and performance-based assessments, supported by artificial intelligence, learning analytics, and gamification. These new methodologies aim to assess not only technical proficiency but also socio-emotional and ethical competencies, such as digital collaboration, online communication, and responsible use of AI tools. Sector-specific analysis reveals differentiated adaptations in education, healthcare, government, and the workforce, with increasing emphasis on dynamic, continuous, and context-sensitive evaluation models. The study highlights persistent challenges, including the digital divide, algorithmic bias, and policy fragmentation, while offering guidance for designing inclusive and scalable assessment systems. As digital ecosystems become more complex and pervasive, the ability to measure digital readiness equitably and meaningfully becomes a central priority for educational research and policy.